2020
DOI: 10.3389/fped.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Necrotizing Enterocolitis Associated With the Single Nucleotide Polymorphisms VEGF C-2578A, IL-18 C-607A, and IL-4 Receptor α-Chain A-1902G: A Validation Study in a Prospective Multicenter Cohort

Abstract: The etiology of necrotizing enterocolitis (NEC) is multifactorial and an underlying genetic predisposition to NEC is increasingly being recognized. A growing number of studies identified single nucleotide polymorphisms (SNPs) of selected genes with potential biological relevance in the development of NEC. However, few of these genetic studies have been replicated in validation cohorts. We aimed to confirm in a cohort of 358 preterm newborns (gestational age <30 weeks, 26 cases of NEC ≥ Bell stage II) the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…25 The IL-1β gene polymorphisms can be associated with various malignancies including gastric cancer, lung cancer and hepatocellular carcinoma, with high expression of IL-1β related to poor survival in cancers. [26][27][28] In our study, we found no significant difference in the distribution of IL-1β (rs16944) polymorphisms between the B-NHL patients and controls. There was no association between IL-1β (rs16944) polymorphisms and clinical manifestations of B-NHL patients.…”
Section: Discussioncontrasting
confidence: 64%
“…25 The IL-1β gene polymorphisms can be associated with various malignancies including gastric cancer, lung cancer and hepatocellular carcinoma, with high expression of IL-1β related to poor survival in cancers. [26][27][28] In our study, we found no significant difference in the distribution of IL-1β (rs16944) polymorphisms between the B-NHL patients and controls. There was no association between IL-1β (rs16944) polymorphisms and clinical manifestations of B-NHL patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Interestingly, both NOD2 and SIGIRR are inhibitors of TLR signaling in the neonatal intestine [ 93 , 98 ]. Genetic variants in the VEGF and other vascular genes might also be potential loci for NEC vulnerability [ 99 ]. Genome-wide transcriptome studies in intestinal tissue obtained from preterm infants with and without NEC also identify innate immune pathways as a key target in NEC [ 100 ].…”
Section: Necrotizing Enterocolitis Pathophysiologymentioning
confidence: 99%
“…Epidemiological studies showed differences in NEC prevalence among populations of different ethnic origin, while a study of twins provided evidence of a familiar predisposition to NEC (3,43,44). Genetic studies reported variations of genes and RNAs involved in NEC pathophysiology, predominantly inflammatory mediators, indicating genetic predisposition to NEC (43,(45)(46)(47)(48). A recent review by Cuna et al refers to the available data on genetic predisposition to NEC (43).…”
Section: Pathophysiology and Current Diagnosis Of Necrotizing Enterocmentioning
confidence: 99%